Testing Means-Tested Aid - Richard Murphy; Gill Wyness (Center for Economic Studies and ifo Institute (CESifo), 2016)
Inequalities do not end once students enter higher education. Yet, the majority of papers on the effectiveness of education aid examine its impact on college enrolment. In this paper, we provide evidence on the causal impact of means-tested financial aid on the outcomes of students who have already enrolled in college. To do so, we exploit a unique non-salient financial aid program which varies both across and within institutions, and for which eligibility is a highly non-linear function of parental income. Our findings suggest that increasing aid by 1,000 increases the chances of gaining a good degree by 3.7 percentage points.
Keywords: I22; I23; I28; 330; higher education; financial aid; degree completion